1997
DOI: 10.1063/1.365194
|View full text |Cite
|
Sign up to set email alerts
|

Role of attractive forces in tapping tip force microscopy

Abstract: We present experimental and numerical results demonstrating the drastic influence of attractive forces on the behaviour of the atomic force microscope when operated in the resonant tapping tip mode in an ambient environment. It is often assumed that tapping is related to repulsive interaction. In contrast, we find that in general the attractive forces are the most dominant interaction in this mode of operation. We show that attractive forces in combination with the repulsive elastic type of forces cause points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(114 citation statements)
references
References 24 publications
(36 reference statements)
8
105
0
Order By: Relevance
“…The same phenomenon happens when the scanning frequency goes from high to low except the jump points are different. Similar phenomena have been observed by Anczykowski et al [16] and Kuhle et al [17]. Figure 2 shows the experimental phase-amplitude ratio relations which are taken from Mogonov and E1ings [15] for soft and stiff materials.…”
Section: Experimental Observationssupporting
confidence: 67%
See 1 more Smart Citation
“…The same phenomenon happens when the scanning frequency goes from high to low except the jump points are different. Similar phenomena have been observed by Anczykowski et al [16] and Kuhle et al [17]. Figure 2 shows the experimental phase-amplitude ratio relations which are taken from Mogonov and E1ings [15] for soft and stiff materials.…”
Section: Experimental Observationssupporting
confidence: 67%
“…Anczykowski et al [16] presented results on amplitude vs. tip-sample separation and showed the existence of hysteresis due to nonlinearity and the transition between attractive and repulsive forces. Kuhle et al [17] demonstrated experimentally the frequency response hysteresis and pointed out the effect of attractive force on this hysteresis using a linear interaction force approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Kühle et al found that several points of instability in the parameter space caused by attractive forces combined with repulsive elastic-type forces resulted in disturbances during image acquisition on hard elastic surfaces [5]. The AM-AFM images generated some protruded artifacts when the probe encountered the high hillock structures.…”
Section: Introductionmentioning
confidence: 99%
“…As several experimental parameters influence the values of the phase shift (Brandsch et al, 1997;Kühle et al, 1997;James et al, 2001;García and Perez, 2002), it is not meaningful to rely on the absolute values, which in our experiments ranged from approximately −20 to +120 degrees. The relative shifts reported here, however, clearly exceed the noise range of the measured signals, (our worst case is shown in Fig.…”
Section: Discussionmentioning
confidence: 96%